Implications and Impact of Prior Authorization Policy on Vancomycin Use at a Tertiary Pediatric Teaching Hospital. Issue 5 (May 2015) - Chan, Shannon; Hossain, Jobayer; Di Pentima, M. Cecilia
Abstract : Background: We evaluated the performance of two consecutive antimicrobial stewardship interventions on vancomycin use. Methods: Prospective audit with intervention and real time feedback to providers were implemented in April 2004. In February 2009, the institutional vancomycin policy was modified requiring preauthorization by the pediatric infectious diseases clinician on-call. Monthly vancomycin use was calculated as doses administered per 1000 patient-days. Results: After 5 years of prospective-audit vancomycin use declined from 378 doses administered/1000 patient-days to 208 doses administered/1000 patient-days (45%). Following the implementation of preauthorization, vancomycin use decreased by an additional 16% in the subsequent 4 years. When compared with the trend of vancomycin use with prospective-audit, the trend of vancomycin use after the implementation of the restriction policy increased by 3.9 doses per month (SE: 1.51, P =0.012) during the subsequent 51 months. Conclusions: Implementation of preauthorization didn't significantly reduce the use of vancomycin beyond the accomplishments by prospective-audit and feedback by a team of an infectious disease pharmacist and physician.